Tracking or lacking? Health app engagement among young adults in Portugal - Eduardo Antunes; Ana Marta M. Flores (methaodos.revista de ciencias sociales)
While digital media have become integral parts of young adults' everyday lives, it remains unclear whether health-focused media, like health apps, hold the same importance. This study explores health app usage patterns among young adults in Portugal, analysing tracking data from 342 participants over 90 days. The main findings reveal that contrary to global trends, engagement with health apps remains relatively low. Although the COVID-19 pandemic led to increased adoption of certain public health-related apps, this surge did not translate into sustained engagement. Gender and regional disparities were the most evident, with women and young adults in Lisbon showing higher usage levels. Additionally, the study highlights that a portion of the health app usage is connected with the COVID-19 context, where those apps function more as tools for navigating institutional requirements—such as COVID-19 certifications—rather than for sustained self-care practices. Our findings challenge assumptions about the widespread adoption of health-tracking technologies and emphasise the need for further research on sociocultural factors shaping digital health engagement in Portugal and beyond.